European integration sharing of experiences - Møller, J. Ørstrøm (Institute of Southeast Asian Studies, 2008)
A clear guide to current EU institutions, practices, and policies, this is also an informed insider's account of how they have emerged in their present form, with clues on future change. The mixture of analysis and history, description and prescription, works well, because the author has had a ringside seat, but retains a cool Nordic non-partisan detachment. The hints he offers to those, for example in Asia, considering following a similar path to regional integration, represent the distilled wisdom of a career in balancing economic benefits and national sensitivities. As his story shows, it can be done. - Lord Kerr, Former Head of the UK Diplomatic Service, now Chairman of Imperial College, London and Deputy Chairman of Royal Dutch Shell.